Income inequality and the erosion of democracy in the twenty-first century - Eli G. Rau; Susan Stokes (Proceedings of the National Academy of Sciences, 2025)
Among the most pressing problems societies face today are economic inequality and the erosion of democratic norms and institutions. In fact the two problems—inequality and democratic erosion—are linked. In a large cross-national statistical study of risk factors for democratic erosion, we establish that economic inequality is one of the strongest predictors of where and when democracy erodes. Even wealthy and longstanding democracies are vulnerable if they are highly unequal (though national wealth might provide some resiliency). The association between inequality and risk of democratic backsliding is robust, and holds under different measures and structures of both income inequality and wealth inequality. The association is unlikely to be a case of reverse causation. For concerned citizens seeking to understand why so many democracies are eroding and how to stop this process, our study indicates that policies for ameliorating inequality are a promising path forward.